RESPON GENERASI MILENIAL PADA KONTEN DAKWAH YOUTUBE AGUS MUHAMMAD IQDAM (ANALISIS NETNOGRAFI) - Hasyim Iskandar; Binti Amanah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
Modern communication tools have made it possible to spread da'wah via the internet more creatively and interestingly. An example is the use of YouTube by the Sabilu Taubah Ta'lim Council to spread Agus Muhammad Iqdam's preaching through the Gus Iqdam Official channel. Since its founding on April 1 2020, this channel has grown rapidly with 706 thousand subscribers and 228 videos. This assembly aims to approach street children and criminals in a carefree and non-formal atmosphere, providing a space for them to learn and strengthen their religious knowledge. To study more deeply related to this research, all data will be analyzed using the netnography analysis method, to find out and understand deeply the meaning, for example, of human practices, culture, works of art and texts, in the netnography method (Digital Ethnography Method in Modern Society), using theory from Rulli Nasrullah Virtual Ethnography Research (Communication, Culture and Sociotechnology Research on the Internet). Netnographic research was chosen because this research uses digital content objects, and intends to reveal reactions that are part of online culture that require online audience interaction on the internet. Researchers will make direct observations on the Gus Iqdam Channel by analyzing the text of the comment column which shows responses regarding his preaching via the YouTube account. This research found that the Gus Iqdam Official YouTube channel received a predominance of positive comments on preaching content with the theme